2006
DOI: 10.1097/01.mlr.0000188913.50489.77
|View full text |Cite
|
Sign up to set email alerts
|

Do Mechanisms that Link Addiction Treatment Patients to Primary Care Influence Subsequent Utilization of Emergency and Hospital Care?

Abstract: These findings suggest that for some treatment modalities, stronger primary care linkage mechanisms decrease subsequent utilization of expensive ED and hospital services. Future study should examine the cost implications of these strong linkage mechanisms and ways to strengthen linkages to off-site medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 32 publications
1
52
1
Order By: Relevance
“…Our results support other studies that theorize integrated care could be of significant value for hard-to-reach populations. 12,13,26,25,60 HIV-infected persons are frequently marginalized from other populations, as are substance users, and studies show they are less likely to use ambulatory care. 34,36 The idea of integrating primary care and substance abuse services is not only practical but also feasible based on the experiences of the FAST PATH Program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results support other studies that theorize integrated care could be of significant value for hard-to-reach populations. 12,13,26,25,60 HIV-infected persons are frequently marginalized from other populations, as are substance users, and studies show they are less likely to use ambulatory care. 34,36 The idea of integrating primary care and substance abuse services is not only practical but also feasible based on the experiences of the FAST PATH Program.…”
Section: Discussionmentioning
confidence: 99%
“…44,51 Linked services have been associated with decreased use of emergency and inpatient hospital services. 13,27,44 Coordinated care has also been shown to increase abstinence rates 27,45 as well as improve addiction-related outcomes. 27 Because integrated primary medical care and substance abuse treatment has the potential to increase quality, improve outcomes, and increase access to services among the substance using population, we developed and evaluated a program of integrated care within the primary care setting for two groups of patients: HIV-infected substance users and substance users at risk for contracting HIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The rationale for investing in these efforts is that high-quality, patient-centric care will not only improve outcomes for HNHC patients, but will also yield dividends in the form of avoided downstream resource utilization. 19,20 In this essay, we offer a clinical vignette highlighting the challenges of caring for HNHC populations. We then describe two primary care approaches for managing HNHC populations: complex case management 21 and specialized clinics focused on HNHC patients.…”
Section: Introductionmentioning
confidence: 99%
“…[139][140][141][142] Studies of colocation have found that patients with addictions who receive both regular addiction and medical care were less likely to be hospitalized than those who received one or neither service, 143 and on-site medical service provision, transportation, and CM increased receipt of medical services. [144][145][146][147][148][149][150] Friedmann et al 151 found that provision of primary medical care by off-site referral or on-site at drug treatment programs, compared with no such mechanism, reduced emergency, and hospital utilization.Furthermore, on-site primary care at addiction programs has been associated with reduced addiction severity. 152 In a randomized trial, patients receiving on-site medical, psychiatric, employment, and family services had less opiate use, and improved medical, employment, legal and psychiatric outcomes.…”
mentioning
confidence: 99%